Comparison of water availability effect on ammonia-oxidizing bacteria and archaea in microcosms of a Chilean semiarid soil - Bustamante, Mauricio; Verdejo, Valentina; Zúñiga, Catalina; Espinosa, Fernanda; Orlando, Julieta; Carú, Margarita (Frontiers in Microbiology, 2012)
Water availability is the main limiting factor in arid soils; however few studies have examined the effects of drying and rewetting on nitrifiers from these environments. The effect of water availability on the diversity of ammonia-oxidizing bacteria (AOB) and archaea (AOA) from a semiarid soil of the Chilean sclerophyllous matorral was determined by microcosm assays. The addition of water every 14 days to reach 60% of the WHC significantly increased nitrate content in rewetted soil microcosms (p<0.001). This stimulation of net nitrification by water addition was inhibited by acetylene addition at 100 Pa. The composition of AOA and AOB assemblages from the soils microcosms was determined by clone sequencing of amoA genes (A-amoA and B-amoA, respectively), and the 16S rRNA genes specific for β-proteobacteria (beta-amo). Sequencing of beta-amo genes has revealed representatives of Nitrosomonas and Nitrosospira while B-amoA clones consisted only of Nitrosospira sequences. Furthermore, all clones from the archaeal amoA gene library (A-amoA) were related to ‘mesophilic Crenarchaeota’ sequences (actually, reclassified as the phylum Thaumarchaeota). The effect of water availability on both microbial assemblages structure was determined by T-RFLP profiles using the genetic markers amoA for archaea, and beta-amo for bacteria. While AOA showed fluctuations in some T-RFs, AOB structure remained unchanged by water pulses. The relative abundance of AOA and AOB was estimated by the Most Probable Number coupled to Polymerase Chain Reaction (MPN-PCR) assay. AOB was the predominant guild in this soil and higher soil water content did not affect their abundance, in contrast to AOA, which slightly increased under these conditions. Therefore, these results suggest that water addition to these semiarid soil microcosms could favor archaeal contribution to ammonium oxidation.